ON THE STRUCTURE OF PALYGORSKITE BY MID- AND NEAR-INFRARED SPECTROSCOPY - Gionis V.; Chryssikos G.D.; Kacandes G.H.; Kastritis I.D. (My University, 2006)
The OH-structural characteristics of an iron-rich palygorskite from Western Macedonia, Greece (Gr-1) and an aluminous palygorskite from Florida (PFl-1) were examined by combined Fourier-transform near-infrared reflectance (NIR) and mid-infrared attenuated total reflectance (ATR) spectroscopy. Analyses of samples heated from ambient to 130 °C allowed for the development of a self-consistent set of band assignments for the structural and surface OH and H2O species of both the hydrated and dehydrated forms. The inner octahedral sites of both samples are largely accounted for by dioctahedral AlAlOH, AlFe3+OH, and Fe3+Fe3+OH pairs. Band intensities for these pairs are consistent with variations in the concentration of octahedral Fe and Al in the two samples. In addition, both samples display a trace trioctahedral signature in NIR, which may be related to local trioctahedral domains, or the presence of sepiolite in trace amounts, or as intergrowths. A surface H2O species typical of the hydrated phase was identified via its NIR combination mode at 5317 cm1. The desorption of this species by heating revealed distinct silanol groups with overtone and combination modes at 7255 and 4575 cm-1, respectively. Mg-coordinated and zeolitic H2O species are strongly coupled in the hydrated phase and give rise to NIR combination modes at 5190 and 5240 cm-1. The removal of zeolitic H2O causes the blue shift of the three dioctahedral OH overtones by ca. 20 cm-1 and the rearrangement of the coordinated H2O manifested by the growth of sharp combination modes at ca. 5215 and 5120 cm-1.
Keywords: FE-RICH; HORMITE; HYDRATION; IR SPECTROSCOPY; NIR SPECTROSCOPY; PALYGORSKITE